Kinetic and equilibrium of U(Ⅵ) adsorption onto magnetic amidoxime-functionalized chitosan beads. (1st July 2018) - Zhuang, Shuting; Cheng, Rong; Kang, Mi; Wang, Jianlong
Abstract: Uranium is used to make nuclear fuels for power generation. Uranium-containing wastewater is produced from fuel fabrication, fuel reprocessing, which resulted in the soil and water pollution. In this study, a cleaner and environmental friendly adsorption material, chitosan, was used to remove uranium from aqueous solution. Magnetic amidoxime functionalized chitosan beads were synthesized, characterized and applied for adsorption of uranium. The adsorption capacity of 117.65 mg/g was achieved at pH = 6, mainly due to coordination ability of amidoxime groups. With an Ms of 21.7 emu/g, the magnetic adsorbents could be fast separated from aqueous solution by the magnetic field. Additionally, the results showed that the adsorption process could be well described by the pseudo-second order kinetic (R 2  = 0.9842) and Langmuir models (R 2  = 0.9995). Finally, an adsorption mechanism was tentatively proposed to explain the adsorption process. Highlights: A cleaner and environmental friendly adsorption material was used to adsorb uranium. Magnetic amidoxime functionalized chitosan beads were synthesized and characterized. The adsorption capacity of 117.65 mg/g was achieved at pH = 6. The adsorption process conformed to second-order kinetic and Langmuir models. Adsorption mechanism was mainly due to coordination ability of amidoxime groups.